Абстрактні простори Бєсова, асоційовані із замкненими операторами в банахових просторах - Дмитришин, М.І.; Лопушанський, О.В. (Видавничий дім "Академперіодика" НАН України, 2007)
We introduce the abstract quasinormed Besov spaces which are based on the concept of exponential type vectors. In the case of a differentiation operator, these spaces coincide with their classical analogs. Using the abstract Besov spaces, we investigate the problem of best approximations of a given closed linear operator in a Banach space by exponential type vectors. Applications of the best approximations by spectral subspaces to the problem are also shown.